THE NEURAL NETWORK BASED DESIGN OF EDGE SUPPORTED REINFORCED CONCRETE SLABS - ARSLAN, A; INCE, R (Civil Comp Press, 1994)
[Abstract Not Available]
2nd International Conference on Computational Structures Technology -- AUG 30-SEP 01, 1994 -- ATHENS, GREECE